Protein kinase D1 (PKD1) phosphorylation on Ser203 by type i p21-activated kinase (PAK) regulates PKD1 localization - Chang, Jen Kuan (2017)
Although PKC-mediated phosphorylation of protein kinase D1 (PKD1) has been extensively characterized, little is known about PKD1 regulation by other upstream kinases. Here we report that stimulation of epithelial or fibroblastic cells with G protein-coupled receptor agonists, including angiotensin II or bombesin, induced rapid and persistent PKD1 phosphorylation at Ser203, a highly conserved residue located within the PKD1 N-terminal domain. Exposure to PKD or PKC family inhibitors did not prevent PKD1 phosphorylation at Ser203, indicating that it is not mediated by autophosphorylation. In contrast, several lines of evidence indicated that the phosphorylation of PKD1 at Ser203 is mediated by kinases of the class I PAK subfamily, specifically 1) exposing cells to four structurally unrelated PAK inhibitors (PF-3758309, FRAX486, FRAX597, and IPA-3) that act via different mechanisms abrogated PKD1 phosphorylation at Ser203, 2) siRNA-mediated knockdown of PAK1 and PAK2 in IEC-18 and Swiss 3T3 cells blunted PKD1 phosphorylation at Ser203, 3) phosphorylation of Ser203 markedly increased in vitro when recombinant PKD1 was incubated with either PAK1 or PAK2 in the presence of ATP. PAK inhibitors did not interfere with G protein-coupled receptor activation-induced rapid translocation of PKD1 to the plasma membrane but strikingly prevented the dissociation of PKD1 from the plasma membrane and blunted the phosphorylation of nuclear targets, including class IIa histone deacetylases. We conclude that PAK-mediated phosphorylation of PKD1 at Ser203 triggers its membrane dissociation and subsequent entry into the nucleus, thereby regulating the phosphorylation of PKD1 nuclear targets, including class IIa histone deacetylases.